Assessing the attitude of surgical trainees towards virtual reality simulation: A national cross-sectional questionnaire study. Issue 3 (August 2022) - Khatkar, Harman; Ferro, Ashley; Kotecha, Sanjeev; Prokopenko, Max; Evans, Ashish; Kyriakides, Jonathon; Botterill, Jonathan; Sangha, Miljyot Singh; See, Abbas; Kerstein, Ryan
Background: We performed a cross sectional study to determine the attitudes of surgical trainees and medical students towards virtual reality (VR) simulation in surgical training. A survey was devised through an iterative process before distribution to surgical trainees, foundation year doctors and medical students through online platforms. Methods: The survey was disseminated within the United Kingdom through social media and email correspondence, in co-operation with national surgical organisations. 91 trainees responded from a variety of clinical specialities. Results: VR technology in surgical training was viewed positively, with 91.3% of trainees agreeing that VR should be both an adjunct in surgical training as well as a competency-based assessment tool. Barriers to access were present, with access notably more challenging for senior surgeons. Conclusion: Virtual reality surgical simulation in surgical training is beginning to emerge as a genuine high-fidelity, low-risk solution to the lack of surgical case volume trainees are currently experiencing.